Organisational, legal and financial bases for scientific activity in higher education institutions of the Ministry of Internal Affairs of Ukraine: problems and solutions based on mathematical and statistical methodology - S. O. Serbenyuk; L. S. Nadopta (Law and Safety)
The work is devoted to the problem of improving the current legislation of Ukraine, in particular, in the area of organisation of contractual scientific research, financing of scientific activities, and testing the results of these activities for further implementation in the work of enterprises, institutions and organisations subordinated to the Ministry of Internal Affairs of Ukraine. The current legal framework on this issue has been analysed. Attention has been paid to the main practical problems and the main ways of solving them have been proposed, taking into account the use of mathematical calculations to establish criteria based on the proposed parameters. The statistics of trends in the development of publication activity of the institutions of the Ministry of Internal Affairs of Ukraine in the Scopus database have been considered.